Transport et parité des sexes - Chantal Duchène (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2011)
– While greater account is increasingly being taken of gender in a variety of areas, little progress has been made in this respect in the transport sector. In both developed and developing countries, our societies are gendered in that women and men play different roles, notably because household chores and children are mainly the preserve of women, which reduces the time they have available for activities for which they are responsible and for the trips they need to make in order to perform these activities.
Keywords: 330